Some physical and hydro-physical characteristics of the dystric cambisoils from “Mavrovo” National Park - Petkovski, Dime; Melovski, Ljupčo; Hristovski, Slavčo; Šušlevska, Marjana (Macedonian Journal of Ecology and Environment, 2008)
Brown forest soils (dystric cambisols) were investigated in beech forest (ass. Calamintho grandiflorae-Fagetum) in Mavrovo National Park on elevation of 1300-1380 m a.s.l. The investigated area is in the moderately cold temperate zone with influence of humid and hold mountain climate. Some of the physical and hydro-physical properties of these soils are presented in this article. Soil texture, soil density (particle and bulk density), porosity, air capacity, water-capacity and hygroscopic moisture were analyzed. Analysis of the soil was amended by some of the basic chemical properties: humus, total N, pH, total and available P and available K content.